Enhanced motivated behavior mediated by pharmacological targeting of the FGF14/Nav1.6 complex in nucleus accumbens neurons - Nolan M. Dvorak; Paul A. Wadsworth; Guillermo Aquino-Miranda; Pingyuan Wang; Douglas S. Engelke; Jingheng Zhou; Nghi Nguyen; Aditya K. Singh; Giuseppe Aceto; Zahra Haghighijoo; Isabella I. Smith; Nana Goode; et al. (Nature Communications)
Abstract Protein/protein interactions (PPI) play crucial roles in neuronal functions. Yet, their potential as drug targets for brain disorders remains underexplored. The fibroblast growth factor 14 (FGF14)/voltage-gated Na+ channel 1.6 (Nav1.6) complex regulates excitability of medium spiny neurons (MSN) of the nucleus accumbens (NAc), a central hub of reward circuitry that controls motivated behaviors. Here, we identified compound 1028 (IUPAC: ethyl 3-(2-(3-(hydroxymethyl)-1H-indol-1-yl)acetamido)benzoate), a brain-permeable small molecule that targets FGF14R117, a critical residue located within a druggable pocket at the FGF14/Nav1.6 PPI interface. We found that 1028 modulates FGF14/Nav1.6 complex assembly and depolarizes the voltage-dependence of Nav1.6 channel inactivation with nanomolar potency by modulating the intramolecular interaction between the III-IV linker and C-terminal domain of the Nav1.6 channel. Consistent with the compound’s effects on Nav1.6 channel inactivation, 1028 enhances MSN excitability ex vivo and accumbal neuron firing rate in vivo in murine models. Systemic administration of 1028 maintains behavioral motivation preferentially during motivationally deficient conditions in murine models. These behavioral effects were abrogated by in vivo gene silencing of Fgf14 in the NAc and were accompanied by a selective reduction in accumbal dopamine levels during reward consumption in murine models. These findings underscore the potential to selectively regulate complex behaviors associated with neuropsychiatric disorders through targeting of PPIs in neurons.